2018
DOI: 10.1093/milmed/usy009
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics of Combat-Associated Small Bowel Injuries

Abstract: We found that two-thirds of service members with small bowel injuries also had a large bowel injury. One-third of the patients required diversion and two-thirds had more than one laparotomy. The pattern of bowel injury significantly affected the need for repeat laparotomy and fecal diversion.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 17 publications
0
9
0
2
Order By: Relevance
“…19,20 Rates of abdominal SSIs typically range from 13%-40% depending on the type of procedure and organ involved, with colorectal procedures constituting the highest SSI risk. 2,[9][10][11][12][13][20][21][22] With battlefield trauma, injury mechanisms include high-energy gunshot wounds or blast injuries, which are not usually observed in civilian trauma. Furthermore, the blast mechanism of injury often inflicts unique wounding patterns and concomitant damage, and the surrounding environment may harbor unique organisms that contaminate wounds.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…19,20 Rates of abdominal SSIs typically range from 13%-40% depending on the type of procedure and organ involved, with colorectal procedures constituting the highest SSI risk. 2,[9][10][11][12][13][20][21][22] With battlefield trauma, injury mechanisms include high-energy gunshot wounds or blast injuries, which are not usually observed in civilian trauma. Furthermore, the blast mechanism of injury often inflicts unique wounding patterns and concomitant damage, and the surrounding environment may harbor unique organisms that contaminate wounds.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, the blast mechanism of injury often inflicts unique wounding patterns and concomitant damage, and the surrounding environment may harbor unique organisms that contaminate wounds. 1,2,13,[23][24][25][26][27][28] As a result, battlefield trauma frequently results in grievous polytrauma, including penetrating abdominal injuries that require initial intervention in an austere environment. Despite these factors, the proportion of abdominal SSIs (14%) observed in our study was at the low end of rates reported in civilian patients with trauma (13%-40%).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations